2001
DOI: 10.1007/s100960100550
|View full text |Cite
|
Sign up to set email alerts
|

Nosocomial Outbreak of Clostridium difficile-Associated Diarrhoea due to a Clindamycin-Resistant Enterotoxin A-Negative Strain

Abstract: A clindamycin-resistant toxin A-negative, toxin B-positive Clostridium difficile strain caused an outbreak among 24 hospitalized patients at the Department of Surgery, the Intensive Care unit, and the Department of Internal Medicine of an 800-bed academic hospital. Nineteen patients had undergone a surgical intervention and all 24 patients received at least one dose of antibiotics prior to the development of Clostridium difficile-associated diarrhoea. Twenty-seven episodes of Clostridium difficile-associated d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
105
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(113 citation statements)
references
References 29 publications
7
105
0
1
Order By: Relevance
“…There have also been smaller outbreaks of ribotype 017 strains in Canada (al-Barrak et al, 1999) and Europe (Drudy et al, 2007;Kuijper et al, 2001). Ribotype 017 strains typically have a truncated version of the tcdA gene and, therefore, only produce functional TcdB, yet are still capable of causing severe disease and are often resistant to multiple antibiotics (Drudy et al, 2007;Spigaglia et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…There have also been smaller outbreaks of ribotype 017 strains in Canada (al-Barrak et al, 1999) and Europe (Drudy et al, 2007;Kuijper et al, 2001). Ribotype 017 strains typically have a truncated version of the tcdA gene and, therefore, only produce functional TcdB, yet are still capable of causing severe disease and are often resistant to multiple antibiotics (Drudy et al, 2007;Spigaglia et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…However, the fact that we picked several colonies on the plate in order to perform the IA decreases the probability of missing a toxigenic strain. On the other hand, toxin Bpositive/toxin A-negative isolates could also have been missed, a type of strain which has been reported to account for up to 3 % of the strains in some studies (Barbut et al, 2002;Kuijper et al, 2001;Samra et al, 2002). Such strains, however, would have been detected by the cytotoxin assay, which has a sensitivity of about 60 % as discussed below.…”
Section: Discussionmentioning
confidence: 99%
“…According to Bauer et al [3], hospitalized patients with diarrhea who have been or who are being treated with antibiotics and cytostatics should always have their feces tested for Clostridium difficile. Kuijper et al [13] reported that diarrhea caused by Clostridium difficile occurs more frequently in elderly patients who have been submitted to surgery and in patients placed in the ICU. In another study, carried out in England, 75% of the cases of intestinal infection caused by Clostridium difficile occurred in patients over 64 years of age [5].…”
Section: Discussionmentioning
confidence: 99%